2012
DOI: 10.1111/j.1442-2050.2012.01336.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of postoperative pulmonary complications through intensive preoperative respiratory rehabilitation in patients with esophageal cancer

Abstract: Postoperative pulmonary complications (PPCs) after esophagectomy have been reported to occur in 15.9-30% of patients and lead to increased postoperative morbidity and mortality, prolonged duration of hospital stay, and additional medical costs. The purpose of this retrospective cohort study was to investigate the possible prevention of PPCs by intensive preoperative respiratory rehabilitation in esophageal cancer patients who underwent esophagectomy. The subjects included 100 patients (87 males and 13 females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 40 publications
1
70
0
4
Order By: Relevance
“…Pre-operative exercise for lung cancer patients was associated with a number of benefits for patients [32]. Prehabilitative versus rehabilitative swallowing or respiratory therapy led to significant benefits for patients with head and neck cancers [33][34][35]. There appears to be a potentially significant advantage to implementing prehabilitation rather than rehabilitation interventions for cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-operative exercise for lung cancer patients was associated with a number of benefits for patients [32]. Prehabilitative versus rehabilitative swallowing or respiratory therapy led to significant benefits for patients with head and neck cancers [33][34][35]. There appears to be a potentially significant advantage to implementing prehabilitation rather than rehabilitation interventions for cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Only one retrospective study has been reported [22] . In this previously reported study, 100 patients who underwent esophagectomy were retrospectively analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes it is warranted to delay surgery to supplement proteins as this might improve wound healing and prevent infections or anastomotic breakdown. Early involvement of physiotherapist to improve physical or cardiopulmonary fitness and a dietician for a good nutritional state seems rational but studies into the effect on outcome are contradictory (14)(15)(16)(17).…”
Section: Preoperative Screening and Optimisationmentioning
confidence: 99%